<span>3x</span>² <span>- 8x -3 = 3x</span>² - 9x + x - 3 =
= 3x² - 9x + x - 3 = 3x* ( x - 3) + 1* (x - 3) =
= 3x * (x - 3) + 1 * (x - 3) = (3x + 1) (x - 3)
Answer (3x + 1) (x - 3)
Answer:
7x + 14
Step-by-step explanation:
the first thing to do is expand the parentheses/brackets.
3(5x + 2) -2(4x - 4) will be
3(5x) + 3(2) -2(4x) -2(-4)
= 15x + 6 - 8x + 8
collect like terms
15x - 8x + 6 + 8 = 7x + 14
the answer is 7x + 14
you simply have to add all of the numbers together, so it'll be 2+5+12+7+1 or 27, therefore the answer is B
Answer:
f(x)=-3x+4
(can't see some of your choices)
Step-by-step explanation:
We want x to be independent means we want to write it so when we plug in numbers we can just choose what we want to plug in for x but y's value will depend on our choosing of x.
So we need to solve for y.
9x+3y=12
Subtract 9x on both sides
3y=-9x+12
Divide both sides by 3:
y=-3x+4
Replace y with f(x).
f(x)=-3x+4